LITERASI ZAKAT DAN INTENSI MEMBAYAR ZAKAT HARTA: UPAYA MENDUKUNG PROGRAM SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Rismayani, Gista; Praptapa, Agung; Herwiyanti, Eliada; Lestari, Puji (LP2M Universitas Perjuangan Tasikmalaya, 2024)
The purpose of this research is to identify the effect of zakat literacy (basic knowledge of zakat and advanced knowledge of zakat) on the intention of MSMEs (muslimpreneurs) to pay zakat in Java. This research used a quantitative method by survey design. The sample is 87 MSMEs (muslimpreneur). The data analysis used multiple analysis regression by SPSS 26. the results were basic knowledge and advanced knowledge of zakat had a significant effect on intention to pay zakat, and zakat literacy had a significant effect on intention to pay zakat. The contribution of this research is practical as a measure to assess the extent of zakat literacy in MSME actors. The theoretical contribution can enrich the relationship between zakat literacy proxied with basic and advanced knowledge and the intention to pay zakat through the theory of planned behavior in MSME (muslimpreneur) in Java. This research is limited to the number of samples and the wide and even distribution of samples.